Evaluación del efecto de tres herbicidas selectivos con tres dosis para el control de malezas en el Cultivo de Chocho (lupinus mutabilis sweet) en post-emergencia en la Unidad Educativa Simón Rodríguez, Parroquia Aláquez, Latacunga, Cotopaxi 2019. - Tercero Tercero, Alexandra Maribel. (2019)
The investigation was carried out in Simón Rodríguez Educational Unit located in Latacunga Canton, with the objective of evaluating the effect of three selective herbicides with three doses (high, medium, low) for weed control in the cultivation of chocho (Lupinus mutabilis Sweet) in post emergency, for which a completely randomized block design with a 3 x 3 + 1 factorial arrangement consisting of 10 treatments with three repetitions with a total of 30 experimental units was used in the field. In the field, the indices to be evaluated were germination percentage (before-after), weed incidence, stem diameter, plant height that were evaluated at 20, 50 and 80 days. The following results were obtained: ten days after the emergence of the chocho, the presence of 2922 weeds such as aspha quinoa, wild basil, turnip, prickly amaranth, nettle, smokehouse, chicken grass, dandelion, canayuyo, common mallow was determined, eight days after the emergence of the chocho growing, the herbicides were applied (Abax, Flex, Verdict). The T5 (H2D2) Flex herbicide treatment with the average dose 0.75 ml controlled the weeds by 99.07% and it did not affect the crop, while the T1 treatment (H1D1) which is the Abax herbicide with the high dose (1 ml) ) was the best since it controlled 99.5% of weeds but affected 38 chocho plants (12%) causing necrosis and reduction of the cultivated population, in the same way treatment T8 (H3D2) the Verdict herbicide with the average dose (0 , 75 ml) controlled weeds by 72.47% and did not affect the crop, while the T0 control where no herbicide was applied has 100% weeds